Revisit of Optimal Donor Number Estimation in the Hong Kong Bone Marrow Donor Registry - Ho, Jenny Chung Yee; Cheung, Stephen Kwok Fan; Lui, Zhongyi; Tang, Ivan Wing Hong; Yang, Wanling; Ip, Patrick; Lee, Cheuk Kwong; Middleton, Derek; Kwok, Janette Siu Yin (Frontiers in Immunology, 2021)
High resolution typing of the HLA-DPB1 locus for patient who requested for hematopoietic stem cell transplantation (HSCT) workup has recently become mandatory by the National Marrow Donor Program (NMDP) in order to facilitate matching between donors and recipients for better outcomes. The likelihood of identifying HLA matched donors in Hong Kong, on top of the existing HLA-A, -B, -C, and -DRB1 loci, is revisited in this study. HLA-A, -B, -C, -DRB1 and -DPB1 genotypes of 5,266 volunteer unrelated Chinese donors from the Hong Kong Bone Marrow Donor Registry (HKBMDR), were included in this study . Matching models were employed to determine the matching probabilities for 10/10(DPB1) and 9/10(DPB1) HLA match. The matching probabilities are 20% at 10/10(DPB1) HLA match and 55% at 9/10(DPB1) match, based on the existing 130,000 donors in the HKBMDR. The likelihoods of match become 27% and 65% respectively, by increasing the registry to 250,000. However, if DPB T-cell-epitope (TCE) model is considered in the matching, the probability will increase to 46% at 10/10 DPB1 permissive mismatching. Our findings provide vital information about the future planning on the targeted recruitment size, HLA typing and search strategies of the donor registry and arose the transplant physicians' acceptability to 9/10(DBP1) or 10/10(DBP1) HLA match. Nevertheless, the marrow donor registry has planned for increasing the registry size and bringing down the age of recruited donors which will ultimately enhance patient outcome.